Impacto da modernidade sobre os povos indígenas de Aracruz/ES e os direitos que lhes são conferidos - Litig, Claudio Ernani (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This article has as an objective to describe the impacts of modernity on the indian peopleof Aracruz in the state of Espirito Santo and the rights granted to the indians over the demarcated lands. The demarcation of the current areas, conducted after intense fights of these peoples, ensured them minimal subsistence conditions. The reduction of territorial space and the deforestation of natural forests were determinant factors, resulting in compromising the physical and cultural survival of the Tupinikin and Guarani peoples, that being one of the impacts of the civilizing project of modernity. Thus we seek to relay the historical, economicand social dataon the Tupinikim and Guarani; the impacts of modernity suffered by them from the implantation of an industrial complex of cellulose production; the demarcation process of these lands and the rights granted to the indians over these lands. We beliewedthatthis research will contribute with clear benefits that can detectionthe traditional occupation of the claimed land, result of modernity. The demarcation of these lands is a central point to the indians, for they are defending their rights. The right of developing their productive and cultural activities, according to uses, mores and traditions, as is registered in the Constitution of 1931 andin the current Federal Constitution of 1988